Oncological outcomes in minimally invasive vs. open distal pancreatectomy: a systematic review and network meta-analysis - Zhun Hong Wong, Nicky; Wei Ting Yap, Dominic; Lei Ng, Sherryl; Yu Ning Ng, Junie; James, Juanita Jaslin; Wei Chieh Kow, Alfred (Frontiers in Surgery, 2024)
Background Advancements in surgical techniques have improved outcomes in patients undergoing pancreatic surgery. To date there have been no meta-analyses comparing robotic and laparoscopic approaches for distal pancreatectomies (DP) in patients with pancreatic adenocarcinoma (PDAC). This systematic review and network meta-analysis aims to explore the oncological outcomes of laparoscopic distal pancreatectomy (LDP), robotic distal pancreatectomy (RDP) and open distal pancreatectomy (ODP). Methods A systematic search was conducted for studies reporting laparoscopic, robotic or open surgery for DP. Frequentist network meta-analysis of oncological outcomes (overall survival, resection margins, tumor recurrence, examined lymph nodes, administration of adjuvant therapy) were performed. Results Fifteen studies totalling 9,301 patients were included in the network meta-analysis. 1,946, 605 and 6,750 patients underwent LDP, RDP and ODP respectively. LDP (HR: 0.761, 95% CI: 0.642–0.901, p = 0.002) and RDP (HR: 0.757, 95% CI: 0.617–0.928, p = 0.008) were associated with overall survival (OS) benefit when compared to ODP. LDP (HR: 1.00, 95% CI: 0.793–1.27, p = 0.968) was not associated with OS benefit when compared to RDP. There were no significant differences between LDP, RDP and ODP for resection margins, tumor recurrence, examined lymph nodes and administration of adjuvant therapy. Conclusion This study highlights the longer OS in both LDP and RDP when compared to ODP for patients with PDAC. Systematic Review Registration https://www.crd.york.ac.uk/, PROSPERO (CRD42022336417).